Materials science and technology : a comprehensive treatment. Volume 17A, Processing of ceramics Part I / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Richard J. Brook - Brook, Richard J.
Vol. 17A Processing of ceramics Part I in 1996